Melvin G. Marcus, 1929-1997 - LaBelle, Joseph C. (ARCTIC, 1997)
[This brief biography chronicles the life and achievements of Dr. Mel Marcus, geographer and climatologist, who died 2 March 1997.] . His copious field work activities included research on glacier environments in Alaska and the Yukon, New Zealand, Mt. Ararat in Turkey, and the mountains of Nepal, Peru and Bolivia, plus vegetation studies in the Grand Canyon and urban environmental studies. He published about one hundred papers, books and book chapters. . At his death he was about to receive the Cullum Geographic Medal of the American Geographical Society, and the Lifetime Achievement Award of the Association of American Geographers. .